A Novel Method for Judging Health/Degradation of Lithium-Ion Batteries. Issue 1681 (7th July 2014) - Kaneko, Futao; Kawakami, Takahiro; Baba, Akira; Shinbo, Kazunari; Kato, Keizo; Miyazaki, Shigetoshi; Shimizu, Koichi; Sato, Kenichi; Hanaoka, Osamu
ABSTRACT: A novel and fundamental method was reported to judge states of lithium ion batteries (LIBs) using the capacitance and the voltage of the cells that were estimated from the real-time currents and voltage characteristics of the cells. We measured the differential capacitance, that is, dQ/dV or delta Q/ delta V that is equal to the currents (I) divided by differential voltages (dV/dt) calculated from the current and the voltage characteristics of the cell during the charging/ discharging, where Q is the charge that flows through the cell, V is the voltage of the cell and t is time. It is thought that the capacitance decrease with the degradation of the cell because the effective area of the electrodes is decreasing due to formation of undesirable compounds. The differential capacitance in some specific voltage range for the LIBs was approximately directly proportional to the state of the degradation of the cell. Therefore, it is concluded that the novel method is very useful to judge the state of the LIBs.